2022
DOI: 10.3390/w14060921
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Lake Response to Extreme Climate Change Using the Coupled MIKE SHE/MIKE 11 Model: Case Study of Lake Zazari in Greece

Abstract: Lakes, either artificial or natural, are greatly important as a component in their catchments’ hydrology, but also as ecosystem service providers. However, due to climate change, they have begun to face numerous problems with their water quality and quantity. Furthermore, general circulation models (GCMs) show future climate change with a reduction in rainfall and increase in temperature. The aim of the current study is to present an application where GCMs and state-of-the-art hydrological modelling system MIK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In fact, there are other river basin systems worldwide, using 1D-HD river models (including coupled models) developed with MIKE DHI software for different purposes: data sensitivity analysis [56], water quality in large river delta [57], and superficial streamslake interactions on a catchment scale [58]. In all these works, as well as in our own study have been demonstrated the reliability, simplicity and effectiveness of 1D-HD models for regional-scale water resource evaluation, planning and management.…”
Section: Discussion (Implications For the Water Resources Management)mentioning
confidence: 99%
“…In fact, there are other river basin systems worldwide, using 1D-HD river models (including coupled models) developed with MIKE DHI software for different purposes: data sensitivity analysis [56], water quality in large river delta [57], and superficial streamslake interactions on a catchment scale [58]. In all these works, as well as in our own study have been demonstrated the reliability, simplicity and effectiveness of 1D-HD models for regional-scale water resource evaluation, planning and management.…”
Section: Discussion (Implications For the Water Resources Management)mentioning
confidence: 99%
“…A key requirement for modelling N and P inputs to receiving waters by input pathways is, therefore, the simulation of runoff components and nutrient displacement at high spatial resolution. Physically based hydrological models for this purpose, such as WaSIM-ETH [34] and MIKE SHE/MIKE 11 [35], are based on the physics of hydrological processes and are suitable for simulations at a regional scale, e.g., for individual mesoscale catchments [36][37][38]. Physically based reactive N and P transport models [39][40][41] belong to the same model type.…”
Section: Introduction and Objectivementioning
confidence: 99%
“…VIC [11] is a large-scale, semi-distributed hydrological model, which can be used for drought assessments; however, it focuses on vertical simulation and lacks horizontal simulation. MIKE [12] produces a better simulation of river flow processes and can be used to assess the inundation effects of floods on river channels; however, its simulations of slope hydrological processes are insufficient. WEP [13] is used for watershed hydrological simulations and can be used to study the impact of land-use changes on the water cycle process; however, its simulation of soil water and groundwater processes need to be improved.…”
Section: Introductionmentioning
confidence: 99%